PENGARUH PENGGUNAAN MEDIA JAM PECAHAN (JAPEC) TERHADAP KEMAMPUAN NUMERASI PADA MATERI PECAHAN SISWA KELAS V SD NEGERI 04 PEMANGKAT TAHUN AJARAN 2024 - Marita Priola; Zulfahita; Dodik Kariadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to: 1) To describe the differences in numeracy abilities in fraction material before and after being taught using fraction clock media (JAPEC); 2) to find out how much influence the use of fractional clock media (JAPEC) has on the numeracy skills in class V students of SD Negeri 04 Pemangkat for the 2024 academic year. The type of research used is quantitative research using the True Experimental Design method with a Posttest-only Control Group design. Design. The samples taken in the research were 23 VA class students. The data collection technique uses a multiple choice question test technique containing indicators of numeracy ability. Data analysis techniques use t-test and effect size. The results of this research are: 1) there is a difference in numeracy ability between classes that use fractional clock media and those that do not use fractional clock media, which is 3.70065 > 2.01537, which means there is a difference in numeracy ability between the experimental and control classes, 2) the use of media Fractional hours (JAPEC) has an effect, but not significantly, on students' numeracy abilities with an effect size of 0.70 and falls into the medium criteria at 0.20 < ≤ 0.80.